The heart’s eye: how mental imagery influences romantic emotion - Cui, Boran; Kong, Yulin; Zhang, Weibo (Frontiers in Psychology, 2025)
IntroductionWhile mental imagery—the capacity to generate perceptual-like experiences in the absence of external stimuli—has been studied in fear and other domains, its influence in romantic emotional experiences has not been directly examined. Based on this hypothesis, we investigated how imagery vividness influences romantic emotions and their physiological underpinnings.MethodsFirstly, we reviewed our previous questionnaire data. Furthermore, we compared individuals with vivid imagery and aphantasia, a condition characterized by the absence of voluntary visual imagery, using electroencephalogram (EEG) and heart rate variability (HRV) during a romantic imagery task.ResultsThose with vivid imagery showed stronger neural markers (larger P3 amplitudes, extended LPPs, reduced occipital alpha activity) and heightened autonomic arousal (increased heart rate, suppressed HRV). Aphantasic participants exhibited muted neural responses and minimal autonomic changes, reflecting weaker emotional embodiment.DiscussionThese findings underscore that vivid visual imagery is a crucial driver of romantic emotional intensity and duration, whereas the absence of imagery can lead to a markedly diminished emotional experience.